SENI KALIGRAFI SEBAGAI MEDIA DAKWAH ISLAM DI INDONESIA - Mandalika Mandalika; Miswar Rasyid Rangkuti (Jurnal Ekshis, 2024)
Preaching is one of the most ideal media for conveying Islamic teachings. The da'wah activity that has been known to the general public is only a verbal delivery to the wider community. In fact, non-verbal communication can also be conveyed in conveying Islamic da'wah. In da'wah there are many ways that can be done both verbally and non-verbally. This non-verbal Da'wah can be applied through the art of writing or often referred to as the art of calligraphy. The method that researchers use is the library research method, namely by collecting literature in the form of journals related to the research topic. The results of the research show that Da'wah using the art of calligraphy is a new alternative in the medium of da'wah, in this way preaching becomes more interesting and efficient. The art of calligraphy in question is not only contemporary calligraphy art but in digital calligraphy art it is also effective and even has a wider reach because it can be implemented on the internet, for this reason this da'wah media is called da'wah bil kitabah.